THE EFFECT OF LIFESTYLE, INVOLVEMENT IN FASHION AND PROMOTION ON CONSUMER IMPULSIVE BEHAVIOR AT TUKU2 STORE JEMBER WOMEN'S FASHION STORE - Putri, Yulisya Salsabila; Sumowo, Seno; Fatimah, Feti (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
Fashion is a term that is usually used to characterize a certain style that is then considered popular in a certain period of time. Generally, the style in question refers to the clothing trends that develop in society at that time. Over time, fashion is not only limited to clothing, but also includes accessories, lifestyle, make-up and hair. In fact, fashion trends are now expanding to the technology and automotive sectors. The implication is that business owners can optimize promotional strategies to attract consumer attention and trigger impulse buying. For example, by giving sudden discounts, presenting limited-time offers, or using attractive visual marketing. In this article, the author in conducting research tries to analyze how the impact of the variables Lifestyle (X1), Fashion Involvement (X2), and Promotion (X3) on Impulse Buying (Y) on consumers of Tuku2 Store Jember, a women's fashion store. The object of this research, in addition to selling directly to consumers, sales are also carried out online. So this study uses a quantitative approach based on the number of samples, namely 96 respondents, where this uses a method in the form of a non-probability sampling method with a purposive sampling technique. Data collection was carried out through several stages of analysis, including data instrument testing, multiple linear regression analysis, classical assumption testing, determination coefficient analysis (R²), and hypothesis testing. The collected data were analyzed using SPSS software version 25. Where the results of the study show that the variables Lifestyle, Fashion Involvement, and Promotion have a good and relevant impact on Impulse Buying on Tuku2 Store Jember consumers.